Efficient planar perovskite solar cells with a conjugated random terpolymer as a novel hole-transporting material. (January 2019) - Seo, You-Hyun; Bang, Su-Mi; Lim, Bogyu; Na, Seok-In
Abstract: We introduce that a conjugated random terpolymer (LGC-D013) with N -alkylthieno[3, 4- c ]pyrrole-4, 6-dione (TPD, the acceptor) and benzodithiophene (BDT) and terthiophene (the donor units) can efficiently function as a novel hole-transporting material (HTM) for high-performance planar perovskite solar cells (PeSCs). The roles of the LGC-D013 HTM on PeSC-performances were examined using filed-emission scanning electron microscope, atomic force microscope, photoluminescence, hole mobility, energy-level diagram, and device-resistances. The LGC-D013 based device produced a high power conversion efficiency (PCE) of 12.22%, which was 22% enhancement compared to the reference poly (3-hexylthiophene) (P3HT) based device with a PCE of 9.53%. These results suggest that the random terpolymer LGC-D013 can be considered as an effective HTM to produce a high-efficiency PeSC. Graphical abstract: Image 1 Highlights: A dopant free hole transporting material (HTM), LGC-D013, is introduced in perovskite solar cells (PeSCs). The LGC-D013 shows a high hole mobility and suitable energy-level matching. The LGC-D013 based PeSC provides a higher cell-efficiency than P3HT based PeSC.